AN ANALYSIS OF JARGONS USED BY THE COMMENTATORS FOUND IN PLAYERUNKNOWN'S BATTLEGROUND MOBILE GAME - Herson, Steven Fresly; Surya, Satyawati; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
PlayerUnknown’s BattleGround Mobile is a shooting and survival game that include a team with four players in a team or squads. However, PlayerUnknown’s BattleGround Mobile game event was started in Kuala Lumpur on 29th November until 1th December 2019. This event has 16 (sixteen) teams from region of South East Asia, Europe, North America, South America, Middle East North Africa, South Asia, Korea and Japan. This event had two commentators for each day on the tournaments. As the object of this study, the researcher analyzed the commentator’s utterances as the purposes of this study are to find the jargon on the PlayerUnknown’s BattleGrounds Mobile game and analyze the word-formation process the jargons that the researcher had found on the commentator’s utterances by using the theory of George Yule (1996). Moreover, this research is using the descriptive qualitative research as the research design on this study. The findings of this study show that there are 22 (twenty-two) words classified as jargon of PUBG Mobile game. And 14 (fourteen) words as the word-formation process, they are categorized as acronyms (5 words), compound (6 words), derivation (2 words), and backformation (2 words).